2018
DOI: 10.1117/1.jmi.5.2.025502
|View full text |Cite
|
Sign up to set email alerts
|

Portable impulse-radar detector for breast cancer: a pilot study

Abstract: Microwave breast imaging is a painless and nonradiation method. This pilot study aimed to evaluate the detective capability and feasibility of a prototype of a portable breast cancer detector using a radar-based imaging system. Five patients with histologically confirmed breast cancers with a minimum diameter of 1 cm were enrolled in this study. The antenna array dome of the device was placed on the breast of the patient in a supine position for 15 min per single examination. The primary endpoint was a detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The designed unit measured mere 19.1 cm × 17.7 cm × 18.8 cm making it a very useful tool for imaging [180]. Further on, in 2018, the portable detector was modified to produce a reduced scan time of merely three minutes from the earlier 15 minutes when the antenna array rotated in steps of 15 degrees [181]. This system could visualize breast tumors with a diameter of 1 cm or more.…”
Section: State-of-the-art In Mwimentioning
confidence: 99%
“…The designed unit measured mere 19.1 cm × 17.7 cm × 18.8 cm making it a very useful tool for imaging [180]. Further on, in 2018, the portable detector was modified to produce a reduced scan time of merely three minutes from the earlier 15 minutes when the antenna array rotated in steps of 15 degrees [181]. This system could visualize breast tumors with a diameter of 1 cm or more.…”
Section: State-of-the-art In Mwimentioning
confidence: 99%
“…We developed a prototype handheld bistatic radar-based system using complementary metal-oxide-semiconductor (CMOS)-integrated circuits [36][37][38][39][40][41]. In a clinical pilot study, this system showed a 100% sensitivity in 5 patients with breast cancer [42]. Information on specificity and causes of false positives using this microwave imaging technology has not yet been clarified.…”
Section: Preliminary Workmentioning
confidence: 99%
“…The observed contrast in the microwave properties of cancerous and healthy breast tissues [3][4][5][6] has sparked research into the use of breast microwave sensing (BMS) as a diagnostic tool to be used for breast cancer screening or as a complementary technique to mammography [1,2]. Several research groups have developed BMS systems and evaluated these systems using both phantom and patient data [7][8][9][10][11][12]. Despite the progress made in BMS research over the past two decades, several challenges remain before the technique can be considered for routine clinical use.…”
Section: Introductionmentioning
confidence: 99%